Undertown - Bukiet, Melvin Jules. (Laura Ann); 1978- 1906-1998. 1952- 1974- (New York Amulet Books, 2013)
Middle schoolers Timothy Murphy and Jessamyn Hazard careen downhill on a sailboat which was being towed through Manhattan and fall into the sewers, where they meet interesting characters before being caught by the evil "queen" of this underground society.
Keywords: Adventure and adventurers -- Fiction; Sailing -- Fiction; Sewerage -- Fiction; Homeless persons -- Fiction; New York (N.Y.)